Automated Tree Detection Using Image Processing and Multisource Data - Grzegorz Dziczkowski; Barbara Probierz; Przemysław Juszczuk; Piotr Stefański; Tomasz Jach; Szymon Głowania; Jan Kozak (Applied Sciences)
This paper presents a method for the automatic detection and assessment of trees and tree-covered areas in Katowice, the capital of the Upper Silesian Industrial Region in southern Poland. The proposed approach utilizes satellite imagery and height maps, employing image-processing techniques and integrating data from various sources. We developed a data pipeline for gathering and pre-processing information, including vegetation data and numerical land-cover models, which were used to derive a new method for tree detection. Our findings confirm that automatic tree detection can significantly enhance the efficiency of urban tree management processes, contributing to the creation of greener and more resident-friendly cities.